Phase transformation and electrochemical charge storage properties of vanadium oxide/carbon composite electrodes synthesized via integration with dopamine. Issue 1 (29th April 2022) - Andris, Ryan; Averianov, Timofey; Pomerantseva, Ekaterina
Abstract: Chemically preintercalated dopamine (DOPA) molecules were used as both a reducing agent and a carbon precursor to prepare δ‐V2 O5 · n H2 O/C, H2 V3 O8 /C, VO2 (B)/C, and V2 O3 /C nanocomposites via hydrothermal treatment or hydrothermal treatment followed by annealing under Ar flow. We found that the phase composition and morphology of the produced composites are influenced by the DOPA:V2 O5 ratio used to synthesize (DOPA) x V2 O5 precursors through DOPA diffusion into the interlayer region of the δ‐V2 O5 · n H2 O framework. The increase of DOPA concentration in the reaction mixture led to a more pronounced reduction of vanadium and a higher fraction of carbon in the composites' structure, as evidenced by X‐ray photoelectron spectroscopy and Raman spectroscopy measurements. The electrochemical charge storage properties of the synthesized nanocomposites were evaluated in Li‐ion cells with nonaqueous electrolytes. δ‐V2 O5 · n H2 O/C, H2 V3 O8 /C, VO2 (B)/C, and V2 O3 /C electrodes delivered high initial capacities of 214, 252, 279, and 637 mAh g –1, respectively. The insights provided by this investigation open up the possibility of creating new nanocomposite oxide/carbon electrodes for a variety of applications, such as energy storage, sensing, and electrochromic devices. Abstract : The crystal structure of vanadium oxide in oxide/carbon nanocomposites and their electrochemical charge storage behavior can be controlled by adjusting the ratio of vanadium to dopamine hydrochloride in the interlayer region of bilayered vanadium oxide precursor synthesized via chemical preintercalation approach. The phase changes are induced during a combination of hydrothermal treatment and high temperature annealing in an inert atmosphere. The dopamine molecules act as both a reducing agent and a conductive carbon precursor that is carbonized during heat treatment processing.